鼓泡器中环戊烷-甲烷-盐水体系水合物的生成动力学 - 吕秋楠; 宋永臣; 李小森 (2016)
The formation kinetics of cyclo-pentane（CP）-methane hydrate in Na Cl solution were studied using a bubbling equipment.The effect of gas-flow rate,temperature and pressure on the hydrate formation rate and the effect of gas-flow rate on the gas conversion